CHARACTERISTICS OF TAND B-CELL SUBPOPULATION PROFILE IN THE PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE TREATED WITH VACCINE AGAINST PSEUDOMONAS AERUGINOSA - A. G. Borisov; A. A. Savchenko; I. V. Kudryavtsev; A. V. Moshev; V. A. Kozlov (Медицинская иммунология)
The aim of this study was to evaluate subpopulational profiles of Tand B-lymphocytes in the patients with chronic obstructive pulmonary disease (COPD) under the influence of a multivalent vaccine against Pseudomonas pathogens, in order to justify its usage as a potential immune stimulator of microbial origin. Sixty patients (39 males and 21 females aged 40 – 58 years old) with verified diagnosis of COPD II-III degree were included into the study group. All the patients received a standard COPD therapy. In accordance with planned treatment, this cohort was divided into two groups using a simple randomization. Group 1 included thirty COPD patients (20 men and 10 women) who received standard treatment. Group 2 consisted of thirty COPD patients (19 men and 11 women) who received treatment according to conventional schedule, but further, they were additionally treated with «Pseudovac» vaccine used as a infection-preventing measure. The «Pseudovac» vaccine was injected, according to appropriate instructions for the drug use. Immunological evaluation was performed three times: at admission, as well as 10 and 20 days of treatment. As a control group, 35 healthy individuals (19 men and 16 women) of a similar age range have been examined. Assessment of Tand Bcellspecific immune phenotypes was determined by means of flow cytometry using direct immunofluorescence of leukocytes whole peripheral blood using specific monoclonal antibodies. We have found that Tand Blymphocyte profiles in the COPD patients are characterized by decreased numbers of T-cells (due to drop in cytotoxic T-cells), and increased B-lymphocyte contents. Relative amounts of NKTand γδT-lymphocytes showed an increase in cases of developing bacterial infection. The T-lymphocyte subpopulations in patients with COPD are characterized by increase in relative numbers of regulatory T-cells, Th2-lymphocytes, and T-cells expressing activation markers. B-lymphocyte population in COPD patients was characterized by increased levels of B2-, B1and memory B-cells, along with reduced levels of CD23-receptor-positive B-lymphocytes. During a standard treatment of infectious and inflammatory disease in COPD patients, there is a tendency to normalization of Tand B-lymphocytes subpopulations. However, T lymphocyte number by the 20th day of treatment proved to be reduced (due to decrease in cytotoxic cells), whereas B-lymphocyte content was increased. Furthermore, the levels of NKTand T-regulatory cells remain high at the standard COPD treatment. The «Pseudovac» vaccine exerts a pronounced immunoactive effect upon adaptive immunity, by means of restoring and/or normalizing Tand B-lymphocyte subpopulations in COPD patients by the 20th day of vaccine treatment.